Safety, Tolerability, and Pharmacokinetics of MEDI4893, an Investigational, Extended-Half-Life, Anti-Staphylococcus aureus Alpha-Toxin Human Monoclonal Antibody, in Healthy Adults - Yu, Xiang-Qing; Robbie, Gabriel J.; Wu, Yuling; Esser, Mark T.; Jensen, Kathryn; Schwartz, Howard I.; Bellamy, Terramika; Hernandez-Illas, Martha; Jafri, Hasan S. (Antimicrobial agents and chemotherapy, 2017)
MEDI4893 is an investigational immunoglobulin G1(κ) monoclonal antibody that specifically binds to and neutralizes alpha-toxin, a key Staphylococcus aureus virulence factor. A triple-amino-acid substitution, M252Y/S254T/T256E, was engineered into the MEDI4893 Fc region to extend its serum half-life. A phase 1, double-blind, dose escalation study was designed to evaluate the safety, tolerability, pharmacokinetics, anti-alpha-toxin-neutralizing activity, and antidrug antibody (ADA) response of MEDI4893 following a single intravenous infusion in healthy adults 18 to 65 years of age. Thirty-three subjects were randomly assigned to receive MEDI4893 at 225 mg ( n = 3), 750 mg ( n = 3), 2,250 mg ( n = 8), or 5,000 mg ( n = 12) or placebo ( n = 7) and were followed for 360 days. Adverse events were mild or moderate in severity; none were serious. The MEDI4893 peak serum concentration increased dose proportionally from 77.2 μg/ml (225-mg dose) to 1,784 μg/ml (5,000-mg dose). The area under the concentration-time curve from 0 to 360 days also increased dose proportionally, from 4,840 μg · day/ml (225-mg dose) to 91,493 μg · day/ml (5,000-mg dose), indicating linear pharmacokinetics. MEDI4893's terminal half-life was estimated to be 80 to 112 days, which is approximately 4-fold longer than the half-lives of other human immunoglobulin G antibodies. The alpha-toxin-neutralizing activity in serum correlated highly with the MEDI4893 concentrations in serum. Three adults transiently tested positive for ADA on day 151, but this did not have an impact on MEDI4893 serum concentrations or the MEDI4893 safety profile; no subjects exhibited serum ADA at the study end. These data support the continued development of MEDI4893 for the prevention of S. aureus -mediated pneumonia. (This study has been registered at ClinicalTrials.gov under identifier NCT02296320.)